2020
DOI: 10.1002/ijfe.2021
|View full text |Cite
|
Sign up to set email alerts
|

Political connections, legal environments and firm performance around the world

Abstract: Theoretically, political connections may be a double‐edged sword to a firm. On the one hand, political connections may help the firm to reduce the policy risk and access to more critical resources. On the other hand, political connections may introduce the government or politicians as influential stakeholders who may impose their own interests on other stakeholders and cause multiple agency conflicts. Although there are many studies have investigated the effects of political connections on firm performance in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 55 publications
0
30
0
1
Order By: Relevance
“…However, firms with the worst legal environment and facing financial constraints have adopted political links. Therefore, these connections significantly positively impact the firm performance (Pang and Wang, 2020). A growing body of the literature shows that firms with boards of director's link with parliament positively impact the firm performance.…”
Section: Political Connection and Firm Performancementioning
confidence: 99%
“…However, firms with the worst legal environment and facing financial constraints have adopted political links. Therefore, these connections significantly positively impact the firm performance (Pang and Wang, 2020). A growing body of the literature shows that firms with boards of director's link with parliament positively impact the firm performance.…”
Section: Political Connection and Firm Performancementioning
confidence: 99%
“…However, some studies verify the negative effect of political connections. Pang and Wang found that political connection will damage the company's future business performance and corporate value, which can be mitigated by a better legal environment or shareholder protection mechanism preventing rent-seeking activities [7]. Gao et al show that politically connected non-family firms have lower M&A performance.…”
Section: Related Researchmentioning
confidence: 99%
“…A similar phenomenon was shown in a study of Mergers & Acquisitions (M&A) deals from 2008 to 2018 related to Chinese listed energy firms (Li et al , 2021) where executives’ political connections have a positive effect on corporate performance only if there are no M&A activities whilst political connections were found to harm firm performance through M&A activities. Pang and Wang (2020) found in a large sample covering 49 countries and 151,475 firm-year observations that political connections have an adverse net effect on the firm’s operating performance, as well as the firm value. They explain that although political connections may provide access to more critical resources, the firm may be imposed by governmental or political interests which cause multiple agency conflicts.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%